Корабль призраков: роман / В. Е. Платова - Платова Виктория Евгеньевна (Детектив, 2006)
Экземпляры: ф.3 (ретро) / Инвентарный номер: 43568 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 37 / ББК: 84(2Рос=Рус)6